2019
DOI: 10.1002/aic.16835
|View full text |Cite
|
Sign up to set email alerts
|

Chelation of transition metals into MOFs as a promising method for enhancing CO2 capture: A computational study

Abstract: Metal organic frameworks (MOFs) are one kind of promising porous materials for CO 2 capture and separation. In this work, the chelation of the first-row transition metals (from Sc to Zn) into MOFs was proposed to enhance its CO 2 adsorption capacity. The adsorption mechanisms and adsorption capacities of CO 2 in the chelated MOFs were explored by using quantum mechanical calculation and QM-based grand canonical Monte Carlo simulations. The results show that the chelation of transition metals can significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Previous studies showed that the chelated transition metal with tetrahedral geometry in the COFs has the most favorable binding strength for hydrogen storage to increase the H 2 storage capacity. 11,23,56…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that the chelated transition metal with tetrahedral geometry in the COFs has the most favorable binding strength for hydrogen storage to increase the H 2 storage capacity. 11,23,56…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the chelated transition metal with tetrahedral geometry in the COFs has the most favorable binding strength for hydrogen storage to increase the H 2 storage capacity. 11,23,56 In the previous section, we have shown that both linker-3-TM-Cl x and linker-5-TM-Cl x have excellent binding enthalpy for more than one H 2 physisorption. Thus, to explore the reason behind the high binding enthalpy, we performed energy decomposition analysis (EDA) and molecular orbital (MO) interaction calculations of both the TM-chelated and the pure linker-3 with the H 2 molecule.…”
Section: Interaction Between Chelated Linkers and H 2 Moleculesmentioning
confidence: 89%
See 1 more Smart Citation
“…Using functional ligands that can interact strongly with metals, such as 2,20-bipyridine (bpy), MOFs with accessible chelating sites can be synthesized. 86 Gonzalez et al 87 synthesized metal chelated MOFs by immersing UiO microcrystalline powder in an acetonitrile solution of metal halide salts (CuCl 2 , CuCl, CoCl 2 , and FeBr 2 ) at 80 °C for 5 days. It was found that these metal-chelated MOFs had the same structure as the parent matrix and permanent pores.…”
Section: Modification Methods Of Mofs For Co2 Capturementioning
confidence: 99%
“…It was found that these metal-chelated MOFs had the same structure as the parent matrix and permanent pores. Hu et al 86 chelated transition metals (from Sc to Zn) into MOFs and used quantum mechanics calculations and QM-based grand canonical Monte Carlo simulations to study the CO 2 adsorption mechanism and capacity. The results showed that the chelation of transition metals could significantly improve the CO 2 adsorption capacity of MOFs under low-pressure conditions.…”
Section: Modification Methods Of Mofs For Co2 Capturementioning
confidence: 99%